Difference Between Sucrose and NaCl Flotation Method for Detecting Soil-Transmitted Helminths (STH) - Ghofur, Abdul; Purnamasari, Cici (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
This in vitro study aimed to compare the detection performance of sucrose and NaCl flotation solutions in detecting Soil-Transmitted Helminths (STH) eggs. A total of 24 pooled stool samples were examined using four treatments: 25% sucrose (specific gravity 1.10), 26% sucrose (specific gravity 1.11), 25% NaCl (specific gravity 1.19), and 26% NaCl (specific gravity 1.20), with six replicates for each treatment. Because the number of eggs found was low, the data were analyzed descriptively using a count data approach based on the positivity rate and the total number of eggs detected. The results showed that in the 25% sucrose, 26% sucrose, and 25% NaCl treatments, no Soil-Transmitted Helminths eggs were found (0/6 replicates; 0%). In contrast, in the 26% NaCl treatment, 3 STH eggs were found in 3 replicates with a positivity rate of 50%, consisting of 2 Ancylostoma duodenale eggs and 1 Trichuris trichiura egg. These results indicate that only the 26% NaCl solution (specific gravity ≥1.20) was capable of detecting Soil-Transmitted Helminths eggs under the conditions of this study. However, the low number of eggs detected is thought to be related to the mild degree of infection, which limited statistical analysis between treatments.